It can't be true a hailstone bigger than a tennis ball! : incredible tactile comparisons - Star, Fleur 1974- (New York, New York DK Publishing, 2016)
Presents a treasury of facts about subjects ranging from animals and the human body to architecture and out space. Every entry is written in both braille and large print
Cover title
The world around us
13
Keywords: Board books; Board books; Braille books -- Specimens; Braille books; Curiosities and wonders -- Juvenile literature; Curiosities and wonders; Textured books -- Specimens; Textured books; Board books; Braille books; Curiosities and wonders; Textured books; Toy and movable books; Juvenile works; Specimens